2012
DOI: 10.4025/cienccuidsaude.v11i1.18859
|View full text |Cite
|
Sign up to set email alerts
|

Grupo de pais da unidade de terapia intensiva pediátrica: percepção dos familiares

Abstract: (HCPA) está inserido no Programa de Apoio à Família, do Serviço de Enfermagem Pediátrica. O objetivo do estudo é conhecer a percepção dos familiares das crianças hospitalizadas sobre o Grupo de Pais. O presente estudo é exploratório-descritivo com enfoque qualitativo e foi desenvolvido dentro do HCPA após aprovação da Comissão de Pesquisa da Escola de Enfermagem e do Comitê de Ética da instituição. A coleta de informações foi realizada no segundo semestre de 2008, por meio de entrevista semiestruturada com nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 5 publications
0
7
0
3
Order By: Relevance
“…Studies developed with groups of parents of children in neonatal and pediatric intensive care units showed that this space was identified as an opportunity to clarify doubts about the family about the clinical conditions of the child and procedures performed for treatment. The information provided by professionals allows family members to feel safe to organize their emotional life, mobilizing internal resources to face the situation (3,7) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies developed with groups of parents of children in neonatal and pediatric intensive care units showed that this space was identified as an opportunity to clarify doubts about the family about the clinical conditions of the child and procedures performed for treatment. The information provided by professionals allows family members to feel safe to organize their emotional life, mobilizing internal resources to face the situation (3,7) .…”
Section: Discussionmentioning
confidence: 99%
“…In these moments of information sharing and clarification of doubts, the participating families observed the behavior and reactions of other families going through similar experiences and identified themselves with the problems of others. These studies have shown that the family attributes positive meaning to the participation in the group, identifying with the doubts of other participants, and reaching the necessary clarification (3,(7)(8) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Os cuidadores podem ter restrições no espaço da terapia intensiva. Esse fato gera frustração em muitos responsáveis e é um dos principais estressores (Hillig & Ribeiro, 2012).…”
Section: Intensiva Pediátricaunclassified